Adaptive reuse of historical buildings: Service quality measurement of Kuala Lumpur museums - Ali, Zuraini Md; Zawawi, Rodiah; Myeda, Nik Elyna; Mohamad, Nabila (Emerald, 2019)
Purpose: The purpose of this paper is to focus on the impacts that the adaptive reuse of historical building has on museum service quality by analysing the visitors’ expectations and perceptions through the HISTOQUAL model. It looks deeper into investigating the enhancement of adaptive reuse approach to historical buildings not only to the surrounding environment, but also to the building’s cultural significance. Design/methodology/approach: A field survey implementing quantitative approach was conducted by using questionnaires to collect the visitors’ expectations and perceptions on their visits to the selected case study sites. The selected two case study sites are both newly adaptive reuse museums located in the heart of Kuala Lumpur. Through these case studies, the visitors’ expectations and perceptions were analysed and the differences were identified. Findings: Positive feedback on the level of service quality provided at both museums indirectly shows the success of adaptive reuse initiative on the historical buildings towards adapting their new functions as a museum. It was also noted that foreign language leaflets and facilities for less able visitors were among the two service criteria that do not exceed the expectations of users. In general, these findings are crucial in identifying the gap within the services provided and appropriate measures that can be undertaken for further improvement. Research limitations/implications: Further study can be employed to a larger population of study to cater for a variety of perspectives from both users and managers of the buildings. Practical implications: This paper highlights the implications of users’ feedback towards building usability and functions. It provided imperative findings from the users’ point of view pertaining to the services provided. Social implications: The paper illustrates the significance of social perceptions on the implications of service delivery. It also reports empirical evidence in highlighting the importance of users’ attributes towards excellent service delivery. Originality/value: Up to present, there exists a small number of studies that look into reviewing the new functions of adaptive reuse buildings. This study now contributes to create a larger number of studies in this scope, especially within the context of Malaysia. © 2018, Emerald Publishing Limited.